2022
DOI: 10.3390/foods11070978
|View full text |Cite
|
Sign up to set email alerts
|

Involvement Theory with Market Segmentation: Effect of False Functional Food Advertising on Purchase Intention

Abstract: In certain cases, people’s health can be compromised or medical treatment delayed as a result of their misplaced belief in false advertisements and purchasing of functional foods. These advertisements can be divided into three distinct types of claims: nutrition, health, and reduction in disease risk. This study analysed how, after consumers realise advertising violations, their intention to purchase functional foods with different claims are affected by the degree of consumer involvement (product, advertising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Another theoretical perspective useful in explaining the role of reasons is involvement theory. Involvement as a motivational concept is related to personal values and needs [76]. Consumers are more likely to be cognitively engaged and to actively evaluate reasons for high-involvement products [13].…”
Section: Moderating Effect Of Reasonsmentioning
confidence: 99%
“…Another theoretical perspective useful in explaining the role of reasons is involvement theory. Involvement as a motivational concept is related to personal values and needs [76]. Consumers are more likely to be cognitively engaged and to actively evaluate reasons for high-involvement products [13].…”
Section: Moderating Effect Of Reasonsmentioning
confidence: 99%
“…Several studies have stated that communication strategies, including advertising and marketing strategies, are driving factors that can influence purchase intentions (Leong and Paim, 2015; Wu et al ., 2022). A study reported by Yeong et al .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several studies have stated that communication strategies, including advertising and marketing strategies, are driving factors that can influence purchase intentions (Leong and Paim, 2015;Wu et al, 2022). A study reported by Yeong et al (2021) explored food disposition and showed a promising trend of consumers being inclined to reduce food waste by taking food home from restaurants or hotels after using a strategic communication tool called 'concept of the doggy bag', a Japanese promotion of the habit of taking leftovers home.…”
Section: Theoretical Background 21 Current Issues In Food Consumption...mentioning
confidence: 99%
“…At the same time, the decision-making behaviours of individuals are influenced by internal and external message cues (i.e. message sender, message type, dissemination motivation, and surrounding environment) (Wu, Liang, and Ip 2022). When a message is posted online, the general public tends to respond in various manners, such as by liking, commenting, clicking, and sharing (Himma-Kadakas 2017).…”
Section: Backfire Effectmentioning
confidence: 99%